Can Cover Crop and Manure Maintain Soil Properties After Stover Removal from Irrigated No‐Till Corn?. Issue 4 (30th June 2014) - Blanco-Canqui, Humberto; Ferguson, Richard B.; Jin, Virginia L.; Schmer, Marty R.; Wienhold, Brian J.; Tatarko, John
Abstract : Addition of cover crops and animal manure following corn ( Zea mays L.) stover removal for expanded uses may mitigate negative soil property effects of stover removal. We studied the short‐term (3 yr) cumulative impacts of stover removal with and without winter rye ( Secale cereale L.) cover crop or animal manure application on near‐surface (0‐ to 5‐cm depth) soil properties under irrigated no‐till continuous corn on a Hastings silt loam (fine, smectitic, mesic Udic Argiustolls) (<3% slope) near Clay Center, NE. Treatments were irrigation levels (full and deficit), amelioration practices (none, cover crop, or animal manure), stover removal (no removal or maximum removal), and N fertilization (125 or 200 kg N ha −1 ). Data collected after 3 yr indicate that stover removal (63%) reduced geometric mean diameter of dry aggregates 93%, increased erodible fraction sixfold, and reduced aggregate stability 32% compared with plots without stover removal. Stover removal from plots with cover crop or manure reduced dry aggregate size and stability and increased erodible fraction compared with plots without removal and amelioration practices, indicating that amelioration practices did not offset stover removal effects. Stover removal reduced wet aggregate stability and soil organic C (SOC) concentration in the 0‐ to 2.5‐cm depth, but cover crop or manure mitigated these small reductions. Stover removal did not change water infiltration rates and had small effects on particulate organic matter (POM). Overall, in the short term, cover crop or manure may not provide sufficient protection from raindrop impact and wetting and drying cycles to maintain soil structure, resulting in increased susceptibility to wind erosion. Use of these amelioration practices, however, may offset changes in surface layer wet aggregate stability and SOC after high rates of stover removal in this region.